(3JbQjH GdZQjHjf (B: ( (3ZQjH GdMOjK dCHi YHjO GdbGSe Hf SdGe hZQjH GdMOjK dGHf bJjHI (B)s - (3CHh GdaJM GdQGRj , Sdje Hf GjhH Hf Sdje, CHh GdaJM,J (B447 (3g` s
(3ChdgG (B:s
(3jHJOF HMQa GdgeRI s
(3BNQgG (B:s
(3hjfJgi Edi MQa GdVGO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B243s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B69 s
Keywords: (3GdMOjK h GdeUWdMs